Fungsi Implikatur Percakapan dalam Acara TV “F.R.I.E.N.D.S”: Pendekatan Pragmatis - Vivian Cristina; Afriana Afriana (Universitas Putera Batam, 2021)
The aimed of this research is to analyze the function of the conversational implicature found in a famous American TV show, named F.R.I.E.N.D.S. The researcher used the conversational implicature theory by Grice (1975) to identify the utterance and the speech acts theory by Searle (1976) to categorize the function. The design of this research is qualitative research. The researcher used the interview method by Sudaryanto (2015) to collect data, the pragmatic identity method by Sudaryanto (2015) to analyze the data, and used the informal presentation method by Sudaryanto (2015) to present the research result. The researcher collected ten data that contain conversational implicature, and two of the data categorized as representatives/ assertives, three data categorized as directives, two data categorized as commissives, two data categorized as expressive, and the remaining data categorized as declarations. The result concludes that out of the ten analyzed data, directives is the most used speech acts in the TV show.